THE ROLE OF THE GULF COOPERATION COUNCIL (GCC) COUNTRIES IN COUNTERING THE IRANIAN THREATS FOR PROMOTING THEIR COMMON SECURITY IN MARITIME DOMAIN - Almutairi, Fahad; Finaud, Marc; Schwok, René; Biava, Alessia (Journal of Humanities & Social Sciences, 2021)
Iran policies pose threats to the security of the Gulf. The Gulf region has witnessed a noticeable tension, as Iran attacked several civilian ships of the Gulf states in an undeclared manner. The GCC countries made major efforts and some joint responses to such threats to achieve maritime security in the Gulf. The current study aims to focus on the role of the Gulf Cooperation Council (GCC) countries in responding to the Iranian threats to maintain their common security in the Gulf maritime domain, which based on the Idea: Iran poses threats to the security in the Gulf, which is prompting the GCC countries for more cooperation and to respond decisively to these threats to maintain their common security in the Gulf maritime domain. This showed that there is an urgent need to strengthen the ties of the Gulf countries to each other, unite and alliance in order to create a military naval coalition which helps to balance power and threat with Iran and provides protection for Gulf waters from any Iranian threats in the maritime domain of the region.